2013
DOI: 10.1371/journal.ppat.1003221
|View full text |Cite|
|
Sign up to set email alerts
|

Trichoderma-Plant Root Colonization: Escaping Early Plant Defense Responses and Activation of the Antioxidant Machinery for Saline Stress Tolerance

Abstract: Trichoderma spp. are versatile opportunistic plant symbionts which can colonize the apoplast of plant roots. Microarrays analysis of Arabidopsis thaliana roots inoculated with Trichoderma asperelloides T203, coupled with qPCR analysis of 137 stress responsive genes and transcription factors, revealed wide gene transcript reprogramming, proceeded by a transient repression of the plant immune responses supposedly to allow root colonization. Enhancement in the expression of WRKY18 and WRKY40, which stimulate JA-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
206
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(232 citation statements)
references
References 80 publications
(108 reference statements)
16
206
1
9
Order By: Relevance
“…Tomato seed treatment with T. harzianum confers protection against oxidative damage, alleviating the biotic, abiotic, and physiological stresses of germinating seeds and seedlings (56). We had observed the upregulation of several genes related to responses against abiotic stresses in Arabidopsis after 24 h of incubation in the presence of T. harzianum (12), and a recent study reported that Trichoderma can induce the expression of APX1 in salt-stressed Arabidopsis plants (57). The slight APX1 upregulation observed in in vitro assays and the absence of significant expression changes in the time course study (data not shown) could be due to the absence of salt-stressed plants in these assays.…”
Section: Discussionmentioning
confidence: 95%
“…Tomato seed treatment with T. harzianum confers protection against oxidative damage, alleviating the biotic, abiotic, and physiological stresses of germinating seeds and seedlings (56). We had observed the upregulation of several genes related to responses against abiotic stresses in Arabidopsis after 24 h of incubation in the presence of T. harzianum (12), and a recent study reported that Trichoderma can induce the expression of APX1 in salt-stressed Arabidopsis plants (57). The slight APX1 upregulation observed in in vitro assays and the absence of significant expression changes in the time course study (data not shown) could be due to the absence of salt-stressed plants in these assays.…”
Section: Discussionmentioning
confidence: 95%
“…The genus Trichoderma includes opportunistic plant symbionts that can colonize the apoplast of the plant roots (Brotman et al, 2013). The counter inhibition of Trichoderma against Fusarium has been observed in vitro, and Trichoderma spp may be used as ideal biocontrol agents (Dube et al, 2007;Poornima, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, more and more evidence has been accumulated that demonstrates that these benefits and effects from Trichoderma applications are much more extensive. Trichoderma is capable of systemically activating plant defence mechanisms including priming, that anticipate pathogen attack [5,57,64,[66][67][68][69]. The reaction of the plant to the BCA is similar to the ISR elicited by rhizobacteria [70][71][72][73][74][75][76].…”
Section: Introductionmentioning
confidence: 99%